Collaborative effects of chlorogenic acid and caffeine on lipid metabolism via the AMPKα-LXRα/SREBP-1c pathway in high-fat diet-induced obese mice. Issue 11 (31st October 2019) - Xu, Meng; Yang, Licong; Zhu, Yanping; Liao, Mingfu; Chu, Lulu; Li, Xin; Lin, Lezhen; Zheng, Guodong
Abstract : The combination of CGA and caffeine exhibits anti-obesity effects and regulates lipid metabolism via the AMPKα-LXRα/SREBP-1c signaling pathway in mice with high-fat diet-induced obesity. Abstract : To investigate the mechanism of the combined effects of chlorogenic acid (CGA) and caffeine on lipid metabolism in high-fat diet-induced obese mice, eighty female ICR mice were randomly divided into eight groups and fed with a high-fat diet with/without CGA and/or caffeine for 14 weeks. The combination of CGA and caffeine effectively decreased body weight gain, intraperitoneal adipose tissue weight, serum LDL-c, FFA, TC, TG, leptin, IL-6 concentrations, and hepatic TG and TC levels and increased the serum adiponectin level. The CGA and caffeine combination also promoted the phosphorylation of AMPKα, inhibited the expressions of transcriptional regulators (SREBP-1c and LXRα), and decreased the expressions of FAS and HMGR. Besides, the expressions of ACO, ATGL and HSL were increased by the CGA and caffeine combinations. The results indicated that the combination of CGA and caffeine had anti-obesity effects and regulated lipid metabolism in high-fat diet-induced obese mice via the AMPKα-LXRα/SREBP-1c signaling pathway. Thus, chronic CGA and caffeine intakes may be potent for preventing obesity.